STI prevalence among women at risk for HIV exposure initiating safer conception care in rural, southwestern Uganda - Pooja Chitneni, Pooja; Bwana, Mwebesa Bosco; Owembabazi, Moran; Neil, Kasey O’; Kalyebara, Paul Kato; Muyindike, Winnie; Musinguzi, Nicholas; Bangsberg, David R; Marrazzo, Jeanne M; Haberer, Jessica E; Kaida, Angela; Matthews, Lynn T. (HHS Public Access, 2020)
Background: Knowledge of STI prevalence and risk factors is important to the development of tenofovir-based pre-exposure prophylaxis (PrEP) and safer conception programming. We introduced STI screening among women at risk for HIV exposure, participating in a safer conception study in southwestern Uganda. Methods: We enrolled 131 HIV-uninfected women, planning for pregnancy with a partner living with HIV or of unknown HIV-serostatus (2018–2019). Women were offered comprehensive safer conception counseling, including PrEP. Participants completed interviewer-administered questionnaires detailing socio-demographics and sexual history. We integrated laboratory screening for chlamydia, gonorrhea, trichomoniasis, and syphilis as a substudy to assess STI prevalence. Multivariable logistic regression was used to determine correlates. Results: Ninety-four women completed STI screening (72% of enrolled). Median age was 30 (IQR 26–34) years, and 94% chose PrEP as part of safer conception care. Overall, 24% had STIs: 13% chlamydia, 2% gonorrhea, 6% trichomoniasis, 6% syphilis, and 3% ≥2 STI. STI prevalence was associated with younger age (adjusted odds ratio [AOR] 0.87, 95% confidence interval [CI] 0.77–0.99), prior stillbirth (AOR 5.04, 95% CI 1.12–22.54), and not feeling vulnerable to HIV (AOR 16.33, 95% CI 1.12–237.94). Conclusion: We describe a 24% curable STI prevalence among women at risk for HIV exposure, planning for pregnancy. These data highlight the importance of integrating laboratory-based STI
Keywords: Sexually transmitted infection; women; PrEP; periconception; Uganda